To find the price at which the quantity demanded equals the quantity supplied, let's solve the equations given:
-
Demand equation: \[ p + 3q = 355 \] (Rearranging gives: \( p = 355 - 3q \))
-
Supply equation: \[ p - 8q = -30 \] (Rearranging gives: \( p = 8q - 30 \))
Now, we set the two equations for \( p \) equal to each other to find the equilibrium quantity \( q \):
\[ 355 - 3q = 8q - 30 \]
Now, combine like terms:
\[ 355 + 30 = 8q + 3q \] \[ 385 = 11q \]
Now, solving for \( q \):
\[ q = \frac{385}{11} = 35 \]
Now that we have the equilibrium quantity, we can substitute this value of \( q \) back into one of the equations to find the equilibrium price \( p \). Using the demand equation:
\[ p = 355 - 3(35) \] \[ p = 355 - 105 \] \[ p = 250 \]
Thus:
- The price at which quantity demanded equals quantity supplied is \( $250 \).
- The equilibrium quantity is \( 35 \) products.
Final results:
a. Price: \( $250 \)
b. Equilibrium quantity: \( q = 35 \)